الصفات الخلقية في وصف خير البرية في القرآن الكريم: دراسة دلالية - أبو حسين، سعدة عبدالفتاح محمد (جامعة الأزهر - كلية اللغة العربية بالقاهرة, 2019)
الحمد لله والصلاة والسلام على سيدنا رسول الله وعلى آله وصحبه ومن والاه.. وبعد. فإن خير ما تصرف فيه الأعمار هو خدمة كتاب الله، والتأمل والتدبر في آياته؛ لذا أحبب أن أكون مع السالكين في بحور المتأملين لمعاني كلمات الله العليم في وصف خير المرسلين في القرآن الكريم، فقد تحدث القرآن الكريم في آيات عديدة عن خصاله الشريفة ما بين خلقية وخلقية، واقتصرت في عملي هذا على الصفات الخلقية في القرآن الكريم تحت عنوان: (الصفات الخلقية في وصف خير البرية في القرآن الكريم دراسة دلالية)، هذا وقد قمت بتقسيم البحث إلى مقدمة، وتمهيد، ومبحثين، وخاتمة، وثبت بأهم المصادر والمراجع، وتحدثت في المقدمة: عن أهمية الموضوع، وسبب اختياره، والصعوبات التي واجهتني، والدراسات السابقة عليه، وكذا المنهج الذي سرت عليه، وأما التمهيد: فقد تحدثت فيه عن مفهوم الأخلاق، وهدفها في الإسلام، وأهميتها، وأما المبحثين: فجاء الأول بعنوان: (تكريم الله – تعالى – لنبيه "صلى الله عليه وسلم" بما وصف به من أسمائه الحسنى وصفاته العليا)، وأما المبحث الثاني: فجاء بعنوان: (ما اختص به "صلى الله عليه وسلم" من صفات في القرآن الكريم عن غيره من الأنبياء والمرسلين)، وأما الخاتمة: فتناولت فيها أهم النتائج التي تم التوصل إليها، ثم ثبت بأهم المصادر والمراجع التي ساعدتني في إتمام هذا البحث، راجية أن أكون قد وفقت في الوصول به إلى مرتبة القبول عند الله – سبحانه – وعند رسوله (صلى الله عليه وسلم)، معتذرة عما لحقه من تقصير، والحمد لله في الأولى والآخرة وصلى الله على نبينا محمد وعلى آله وصحبه وسلم.
Thank God and peace and prayers on our Lord, the Messenger of God, his god and his companions, and god, And yet... The best thing that the ages have done is to serve the Book of God, meditate and reflect on his verses, so I would like to be with those who are in the seas meditating on the meanings of god's words in describing the best of the messengers in the Holy Qur'an. This is based on the creative qualities of the Qur'an under the title: (The creative qualities in the description of the good wilderness in the Qur'an is a semantic study), and I have divided the research into an introduction, a preface, two subjects, and a conclusion, and it was proved by the most important sources and references, and i spoke in the introduction: the importance of the subject, and the reason for its choice, The difficulties i faced, and the previous studies on it, as well as the approach i have followed, and the introduction: in which I talked about the concept of morality, its purpose in Islam, and its importance, and the two topics: the first came under the title: "Honoring Allah-Almighty-Nabih", with what he described as his good names. With regard to the second thesis, it was entitled: "What he has specialized in in the Qur'an from other prophets and missionaries," and the conclusion dealt with the most important results reached, and then proved by the most important sources and references that helped me in completing this research, Rajya. To have succeeded in bringing him to the level of acceptance of Allah, Almighty, and his Messenger (peace be upon him), apologizing for his shortcomings, and thanking God in the first and the afterlife, and praying to God on our Prophet Muhammad and to his god and companions and peace.
Keywords: القرآن الكريم -- تفسير القرآن -- الصفات الخلقية -- شمائل المصطفى